Understanding the effect of controlling phosphorothioate chirality in the DNA gap on the potency and safety of gapmer antisense oligonucleotides. Issue 4 (25th January 2020) - Østergaard, Michael E; De Hoyos, Cheryl L; Wan, W Brad; Shen, Wen; Low, Audrey; Berdeja, Andres; Vasquez, Guillermo; Murray, Susan; Migawa, Michael T; Liang, Xue-hai; Swayze, Eric E; Crooke, Stanley T; et al.
Abstract: Therapeutic oligonucleotides are often modified using the phosphorothioate (PS) backbone modification which enhances stability from nuclease mediated degradation. However, substituting oxygen in the phosphodiester backbone with sulfur introduce chirality into the backbone such that a full PS 16-mer oligonucleotide is comprised of 2 15 distinct stereoisomers. As a result, the role of PS chirality on the performance of antisense oligonucleotides (ASOs) has been a subject of debate for over two decades. We carried out a systematic analysis to determine if controlling PS chirality in the DNA gap region can enhance the potency and safety of gapmer ASOs modified with high-affinity constrained Ethyl (cEt) nucleotides in the flanks. As part of this effort, we examined the effect of systematically controlling PS chirality on RNase H1 cleavage patterns, protein mislocalization phenotypes, activity and toxicity in cells and in mice. We found that while controlling PS chirality can dramatically modulate interactions with RNase H1 as evidenced by changes in RNA cleavage patterns, these were insufficient to improve the overall therapeutic profile. We also found that controlling PS chirality of only two PS linkages in the DNA gap was sufficient to modulate RNase H1 cleavage patterns and combining these designs with simple modifications such as 2′-OMe to the DNA gap resulted in dramatic improvements in therapeutic index. However, we were unable to demonstrate improved potency relative to the stereorandom parent ASO or improved safety over the 2′-OMe gap-modified stereorandom parent ASO. Overall, our work shows that while controlling PS chirality can modulate RNase H1 cleavage patterns, ASO sequence and design are the primary drivers which determine the pharmacological and toxicological properties of gapmer ASOs.